Bacterial Contamination and Antimicrobial Resistance in Two-Spotted (Gryllus bimaculatus) and House (Acheta domesticus) Cricket Rearing and Harvesting Processes - Mitchaothai, Jamlong; Grabowski, Nils T.; Lertpatarakomol, Rachakris; Trairatapiwan, Tassanee; Lukkananukool, Achara (My University, 2024)
Food safety for cricket production is a crucial factor in producing edible crickets with safety for consumers and sustainability for two-spotted (Gryllus bimaculatus) as well as house (Acheta domesticus) cricket production. This study was conducted by simultaneously rearing two cricket species, comprising two-spotted crickets (G. bimaculatus) and house crickets (A. domesticus). A total of 16 rearing crates were used for the present study, which were allocated into 8 rearing crates for each studied cricket species, including paper egg cartons. Cricket eggs were incubated in the rearing crates. Once the crickets hatched, tap water and powdered feed were provided ad libitum throughout the experiment. At the end of this study (35 and 42 days for the two-spotted and house crickets, respectively), all crickets were harvested, rinsed in tap water, and boiled in water for 5 min. During the rearing and harvesting processes, samples were collected from various potential contamination points for bacteria, including E. coli and Salmonella spp. There were samples of the initial input (feed, drinking water, and staff hands), rearing environment (water pipe, crate wall, living cartons, frass, and cricket surface), and harvesting crickets (harvested, washed, and boiled crickets), with a 2-week sampling interval, except for the last round of sampling for the two-spotted crickets. Subsequently, all samples were submitted to isolate and identify contaminated bacteria. The samples from the last round of sampling for both kinds of crickets were submitted to quantify the level of contamination for E. coli and Salmonella spp., including antimicrobial resistance by the disk diffusion method for the positive isolate. The results showed that bacterial contamination was found in the rearing of both cricket species, primarily involving Klebsiella spp. and Enterobacter spp., mainly found in prepared drinking water and the water pipes of drinking water supply equipment, which are potential sources of contamination with cricket frass. E. coli was found in 4.8% and 4.3% of the two-spotted and house crickets, respectively, while no presence of Salmonella spp. was detected in any submitted samples. The quantification of E. coli and Salmonella spp. indicated E. coli contamination near the water pipe and the frass of two-spotted crickets, but Salmonella spp. was undetectable in both two-spotted and house crickets. The antimicrobial resistance of isolated E. coli mainly involved penicillin G, amoxicillin, ampicillin, erythromycin, lincomycin, and tiamulin. Thus, good farm management with proper sanitation practices (such as cleaning and keeping the environment dry), as well as boiling crickets during the harvesting process, may help ensure the safety of edible cricket production.
Keywords: antimicrobial resistance; bacterial contamination; house cricket (Acheta domesticus); rearing and harvesting processes; two-spotted cricket (Gryllus bimaculatus)